2004
DOI: 10.1124/mol.104.000125
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and Degradation of Neuronal Nitric-Oxide Synthase in Vitro: Dimer Stabilization Protects the Enzyme from Proteolysis

Abstract: It is established that neuronal NO synthase (nNOS) is ubiquitinated and proteasomally degraded. The metabolism-based inactivation of nNOS and the inhibition of heat shock protein 90 (hsp90)-based chaperones, which are known to regulate nNOS, both lead to enhanced proteasomal degradation of nNOS. The mechanism of this selective proteolytic degradation, or in essence how the nNOS becomes labilized and recognized for ubiquitination and subsequent degradation, has not been determined. In the current study, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…Supplementation of BH4 stabilizes the functionally active, dimeric form of nNOS in vitro. BH4 also inhibits monomerization of nNOS, as well as inactivation of the enzyme (11,20). Our in vivo data, for the first time, have shown that dietary BH4 supplementation restores both nNOS dimerization and enzyme activity in diabetic rat stomach.…”
Section: Discussionmentioning
confidence: 62%
“…Supplementation of BH4 stabilizes the functionally active, dimeric form of nNOS in vitro. BH4 also inhibits monomerization of nNOS, as well as inactivation of the enzyme (11,20). Our in vivo data, for the first time, have shown that dietary BH4 supplementation restores both nNOS dimerization and enzyme activity in diabetic rat stomach.…”
Section: Discussionmentioning
confidence: 62%
“…In insulin-resistant skeletal muscle, we found that nNOS was actively degraded by the proteasome [37], as demonstrated by the presence of high amounts of ubiquitinated nNOS and by the effect of the inhibitor MG 132, which was able to restore nNOS expression and catalytic activity to a normal level. We also detected lower amounts of SDS-resistant dimers in fa/fa vs fa/+ skeletal muscle (data not shown), which might favour increased susceptibility to proteasomal degradation; indeed, dimerisation is known to protect nNOS from proteolysis [38]. The specific signals targeting nNOS to the proteasome have not been clearly identified.…”
Section: Discussionmentioning
confidence: 90%
“…nNOS overexpression could be due to an enhanced activity of transcription factors, as nuclear factor kappa-B (NFκB) and cAMP response element (CRE) are reportedly involved in nNOS induction [24][25][26]. In addition, the dimeric conformation of nNOS has been shown to protect the protein from proteolysis by the ubiquitinproteasome pathway [27]. However, despite a sevenfold increase in nNOS protein level, we found only a 2.7-fold increase in phospho-Ser847 in fa/fa rats, which plays probably only a minor role in the relative reduction of nNOS activity.…”
Section: Discussionmentioning
confidence: 99%